STUDY BY NONDESTRUCTIVE METHODS OF DEGRADATION OF METALATED SURFACES - A. G. Kulikov; V. V. Filatov; A. A. Ketkovich (Литьë и металлургия)
The results of investigation of degradation of Al and Zn coverings on steel samples, carried out by the authors with application of gravitational method, are given.